Pemikiran Tafsir Progresif: Pendekatan Hermeneutika dalam Memahami Ulumul Quran - Rahmawati, Faiz (https://www.ejournal.smaamc.sch.id/index.php/belajar, 2025)
This research examines the application of the hermeneutic approach in progressive tafsir to understand ulumul Quran in the contemporary era. Progressive tafsir, which focuses on social, cultural and historical contexts, seeks to provide a more relevant understanding of the Qur'anic text. In this study, a descriptive qualitative approach is used to analyse how progressive tafsir is applied in responding to the challenges of the times, such as issues of gender equality, religious pluralism, and human rights. The research data sources consist of progressive tafsir texts and in-depth interviews with tafsir experts, academics, and practitioners of Islamic thought. The purpose of this study is to explore how progressive tafsir uses a hermeneutical approach to produce an understanding that is more applicable and responsive to social dynamics. The results show that although progressive tafsir has great potential in providing solutions to contemporary problems, public acceptance of this tafsir is still limited, mainly due to the dominant influence of traditional tafsir. However, this study confirms that progressive tafsir with a hermeneutic approach can make a significant contribution in developing Islamic thought that is more inclusive and adaptive to changing times, as well as renewing understanding of the Qur'an contextually.